2023
DOI: 10.1101/2023.02.03.527018
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for inhibition of mycobacterial ATP synthase by squaramides and second generation diarylquinolines

Abstract: Mycobacteria, such asMycobacterium tuberculosis, depend on the activity of adenosine triphosphate (ATP) synthase for growth. The diarylquinoline bedaquiline (BDQ), a mycobacterial ATP synthase inhibitor, is an important medication for treatment of drug-resistant tuberculosis but suffers from off-target effects and is susceptible to resistance mutations. Consequently, both new and improved mycobacterial ATP synthase inhibitors are needed. We used electron cryomicroscopy and biochemical assays to study the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In their paper, Courbon et al (2023) also examined the activity of squaramide SQ31f on M. smegmatis ATP synthase. SQ31f inhibited ATP hydrolysis without restoring hydrolysis at high concentrations and did not dissipate the PMF in acidified IMVs, contrasting the diarylquinolines compounds.…”
Section: Figure Mycobacterial Atp Synthase and Its Inhibition By Diar...mentioning
confidence: 99%
See 4 more Smart Citations
“…In their paper, Courbon et al (2023) also examined the activity of squaramide SQ31f on M. smegmatis ATP synthase. SQ31f inhibited ATP hydrolysis without restoring hydrolysis at high concentrations and did not dissipate the PMF in acidified IMVs, contrasting the diarylquinolines compounds.…”
Section: Figure Mycobacterial Atp Synthase and Its Inhibition By Diar...mentioning
confidence: 99%
“…The authors noted that this result was surprising since TBAJ‐876 was reported to not induce uncoupling of the PMF (Sarathy et al , 2020). To further probe the activity of these diarylquinoline compounds, Courbon et al (2023) reconstituted M. smegmatis ATP synthase in inverted membrane vesicles (IMVs), which would mimic a lipid bilayer environment. They make two key observations: (i) restoration of hydrolytic activity does not occur when the enzyme is in a lipid bilayer and therefore is an artifact of detergent solubilization, and (ii) TBAJ‐587 and TBAJ‐876 are able to dissipate PMF in acidified IMVs, though at a slower rate compared to BDQ.…”
Section: Figure Mycobacterial Atp Synthase and Its Inhibition By Diar...mentioning
confidence: 99%
See 3 more Smart Citations